Morphology and AFM Spectroscopy of Irradiated Interface of Silicon - Lamichhane, SK (Nepal Journal of Science and Technology, 2014)
In covalent solids, more energetic irradiation sources are necessary to produce detectable level of damage. The atomic force microscopic (AFM) studies of mega electron-volt (MeV) ions irradiated silicon surfaces have been studied to a fluence of 5×108 ions cm-2 and surface morphology has been studied with AFM. Interesting features of cracks of ~ 50 nm in depth and ~ 100 nm in width have been observed on the irradiated surface. The features seemed to have been caused by the irradiation-induced stress in the irradiated regions of the target surface. The observed feature of cracks seems to be mainly due to the high electronic energy loss of the irradiated ions on the surface induces the stress in it. It confirms that the coarseness of the microstructure of a material directly affects the mechanical properties. DOI: http://dx.doi.org/10.3126/njst.v14i2.10430 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 155-160